Answer:
The standard form of y = 3 x + 1 is -3x + y = 1 .
The standard form of y = 4x - 7 is -4x + y = -7.
Explanation:
Here the given equation are:
y = 3 x + 1
and y = 4x - 7
The above equations are of the form: y = m x + C
Now, the STANDARD FORM of the equation is Ax + By = C
Consider equation 1:
y = 3 x + 1
or, y - 3x = 1
or. -3x + y = 1
⇒ The equation -3x + y = 1 is in STANDARD FORM.
Consider equation 2:
y = 4 x - 7
or, y - 4x = -7
or. -4x + y = -7
⇒ The equation -4x + y = -7 is in STANDARD FORM.